2016
DOI: 10.1021/acs.joc.6b01998
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Characterization of Highly Fluorescent Polycyclic Azaborine Chromophores

Abstract: Six new heteroaromatic polycyclic azaborine chromophores were designed, synthesized, and investigated as easily tunable high-luminescent organic materials. The impact of the nitrogen-boron-hydroxy (N-BOH) unit in the azaborines was investigated by comparison with their N-carbonyl analogs. Insertion of the N-B(OH)-C unit into heteroaromatic polycyclic compounds resulted in strong visible absorption and sharp fluorescence with efficient quantum yields. The solid-state fluorescence of the heteroaromatic polycycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…The last molecule in the series is the abitud molecule. Its structure has been described by Saint-Louis et al [8] who reported a formal single B-N bond as a part of the sixmember ring (see Scheme 1). The molecule contains an unusual N-BOH fragment [8] and intramolecular hydrogen bond, C=O ... H-O.…”
Section: The Double B=n Bondmentioning
confidence: 92%
See 2 more Smart Citations
“…The last molecule in the series is the abitud molecule. Its structure has been described by Saint-Louis et al [8] who reported a formal single B-N bond as a part of the sixmember ring (see Scheme 1). The molecule contains an unusual N-BOH fragment [8] and intramolecular hydrogen bond, C=O ... H-O.…”
Section: The Double B=n Bondmentioning
confidence: 92%
“…In the second part of the research, ten organoboron molecules, i.e., cojwaa [39], cofvuo [47], sictii [58], yecvor [40], axuviy [70], zeypuo [71], bpampb [48], iditas [72], abitud [8], and notlud [73] have been investigated as molecules potentially containing double B=N bonds. Optimized r opt (B,N) bond lengths are between 1.269 Å in cojwaa and 1.455 Å for one of the BN bonds in the ring of iditas.…”
Section: The Double B=n Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecule has a crystallographic center of inversion, as does its close structural counterpart 1,5‐dihydroxyanthraquinone ( 8 ) . The most striking comparison of the X‐ray structure of 7a with those of the hydantoin product 1 and a 3‐pyrrolin‐2‐one adduct 9 is the B─O─H···O═C hydrogen bond distance, which at 1.824 Å in 7a is much shorter than that at 2.225 Å in 1 and 2.239 Å in 9 . This is because the C═O acceptor for H‐bonding to the B─OH group is in a six‐membered ring fused to the boron heterocycle in 7a , whereas it is in a five‐membered ring in 1 and 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Another is the unanticipated production of the bicyclic boron heterocycle 2 from a Horner–Wadsworth–Emmons olefination of 2‐formyl‐4‐methoxyphenylboronic acid and N ‐Cbz protected phosphonoglycine trimethylester, despite running the reaction under Cu‐catalyzed conditions designed to favor indole ring formation . Finally, the condensation of 2‐formylphenylboronic acids with isoindolinones enabled ready access to a collection of fluorescent tetracyclic boron heterocycles like 3 . The goal of the work described herein was to explore and expand the scope of similar reactions of 2‐formylphenylboronic acids with active methylene reagents and, in particular, to take advantage of microwave‐accelerated conditions that could make the production of new boron heterocycles easy and rapid.…”
Section: Introductionmentioning
confidence: 99%